INTEGRASI NILAI-NILAI SYARIAH DALAM SISTEM KEWARISAN DI ERA MODERN: KAJIAN TERHADAP KEBERLANJUTAN DAN TANTANGANNYA - Ropiah, Siti (AS-SALAM, 2025)
Abstract: This study aims to evaluate the extent to which Shariah values can be integrated into the current inheritance system and the challenges faced in the process, such as differences in interpretation, gender equality, and adaptation to state law. The integration of Shariah values into the modern inheritance system has become a significant issue in efforts to establish a fair and relevant governance of inheritance amidst social change. This study highlights the sustainability aspects of a Shariah-based inheritance system and its challenges, such as legal pluralism, cultural resistance, and the complexity of interpreting religious texts. Gender equality is a central issue in discussions of the modern inheritance system based on Shariah. Although Islamic law provides mechanisms for asset distribution designed to protect women's rights, traditional interpretations are often viewed as insufficient in supporting equality. This challenge calls for the reinterpretation of Islamic inheritance law aligned with the principles of maqasid al-shariah, namely justice, the protection of human rights, and social welfare. Moreover, cultural barriers are a significant factor influencing the sustainability of Islamic inheritance law implementation. In some societies, local customs often conflict with Shariah rules, creating tensions between religious law and cultural practices. In this context, a contextual approach and intercultural dialogue are necessary to create harmony between the two. The methodology employed is a qualitative approach with normative and empirical legal analysis. The findings indicate that the integration of Shariah values contributes to the creation of an inheritance system that is fair, inclusive, and relevant but faces challenges such as cultural resistance, legal pluralism, and the dynamics of Shariah interpretation. Keywords: Shariah Values, Modern Inheritance, Sustainability, Challenges, Justice